An experimental setup for physiological evaluation of face mask - Joseph, Frank Gerard (Nanyang Technological University, 2021)
The COVID-19 pandemic has increased public awareness on the importance of using face masks to control the spread of diseases. This had resulted in increased public interest in face mask construction and effectiveness to prevent the spread of airborne pathogens. For many years prior to COVID-19, face mask manufacturers have tried to quantify the effectiveness of face masks through various tests and experiments. Earlier tests in the 1960s conducted on live test subjects allowed the masks to be tested in real physiological conditions but struggled to produce consistent repeatable results. These tests continued to evolve till the current industrial standards and methods were able to provide highly reliable and consistent testing processes. As a result the current testing process has not been changed or improved for many years. Although reliable and consistent, the current test method fails to test the mask under human physiological conditions and instead has become an assessment of the effectiveness based on the material used. This project aims to improve the long-used face mask testing methods and processes to better evaluate the efficacy of a face mask while considering the physiological variables when tested in a near-human environment. A simplified version or the current testing method was created with a repurposed cardiac pump. An assessment was then conducted to determine the feasibility of the pump to be used in the experimental setup as well as the feasibility for the project to be continued given what was achieved and the feasibility of potential future developments. The results of the assessment showed that the cardiac pump was feasible to be used. Additionally, it was determined that it is feasible for further improvements and experimental analysis to be conducted to achieve a testing process that accurately evaluates the effectiveness of a face mask in full physiological conditions.